Behaviour of horses and cattle at two stocking densities in a coastal salt marsh - Nolte, S.; van der Weyde, C.; Esselink, P.; Smit, C.; van Wieren, S. E.; Bakker, J. P. (Journal of coastal conservation, 2017)
Livestock grazing has been practiced in salt marshes in the Wadden Sea area since 600 B.C. Currently livestock grazing is also applied for conservation management. However, effects of such grazing management on salt marshes are likely to vary depending on the species of livestock and stocking density due to differences in the behaviour of the animals. Yet, little is known about the behaviour of different livestock species and stocking densities grazing in salt marshes. We studied the grazing behaviour of horses and cattle by focal observation in an experiment with four different grazing treatments on a coastal salt marsh. In all treatments we recorded diet choice, movement and grazing activity, and spatial distribution. Livestock species shared an overlap in diet choice. Yet, horses more often foraged on the short grass Puccinellia maritima, while the cattle diet contained a higher amount of Aster tripolium. Horses travelled longer distances per day and spent more time grazing than cattle. Spatial distribution of cattle was significantly clustered, while horses showed a random distribution utilizing the whole area. Animal behaviour differs between livestock species and stocking densities with respect to diet choice, activity and spatial distribution.